Enhanced nutrient uptake in rice-wheat cropping system through the use of microbial inoculations and zinc fertilization - Shahane, Amit Anil; Shivay, Y S (Indian Farming, 2022)
Considering the contribution of rice-wheat cropping system to food and nutritional security, the nutrient requirement and uptake potential is needed to study in the face of changing cultivation practices and input addition. Our study involve the treatments of six different cultivation methods and nine nutrient management options showed that system nutrient uptake of nitrogen (N), phosphorus (P), potassium (K), zinc (Zn) and iron (Fe) was 148.4–275.5 kg ha–1, 22.0– 9.0 kg ha–1, 152.8–248.2 kg ha–1, 475.1–835.5 g ha–1 and 4.46–6.03 kg ha–1, respectively in RWCS. The highest nutrient uptake was in the aerobic rice system (ARS) followed by the zero tillage wheat (ZTW) system. Among the nutrient management options, the highest uptake of N, P, K, Zn and Fe was found in recommended dose of nutrient (RDN) (120 kg N ha–1 and 25.8 kg P ha–1) + Zn (5 kg Zn ha-1 through zinc sulphate heptahydrate) which remained at par with application of 75% RDN + Anabaena-Pseudomonas biofilmed formulation + Zn indicating the significance of microbial inoculation in enhancing the nutrient uptake.